Facilitating Political Stability: Cohabitation of non-legalistic Islam and the Moroccan monarchy - Švedkauskas, Žilvinas (Studia Orientalia Electronica, 2017)
Focusing on the role of non-legalistic Islam (Sufism and popular Islam), this paper aims to provide an explanation for the distinctness of Morocco defined by increasing political stability and decreasing group grievances, contrasting with the situation in other countries of North Africa. Based on fieldwork carried out in March 2015, this study employs segmentary theory and the “Governance of Religion” approach in constructing an analytical model explaining cohabitation between the Moroccan monarchy and actors of non-legalistic Islam. Results of the research reveal that 1) actors of non-legalistic Islam in Morocco, though representing a variety of organizational structures and political orientations, can be divided into two groups: traditional vs. reformed non-legalistic Islam. 2) This religious distinction is important politically. For example, actors of traditional non-legalistic Islam can provide social services in the Moroccan periphery or create a background for regional “religious diplomacy”. However, they are not able or willing to include members of the wider society. In contrast, actors within reformed non-legalistic Islam aim to mobi- lize new followers for political causes. 3) Consequently, the Moroccan monarchy seems to apply various governance tools in regulating or co-regulating these actors; these tools include, among other things, direct funding, the co-optation of leaders, and sanctions. Analysis shows that actors representing non-legalistic Islam are engaged in the social life of the country and that this engage- ment results in cohabitation with the Moroccan monarchy. As this paper argues, this cohabitation facilitates political stability and prevents an increase of group grievances.